Quantity surveying practice - Seeley, Ivor H. (The Macmillan Press Ltd, 1984)
This book covers the whole range of skills and knowledge that modern quantity surveyors require to perform their work efficiently and effectively. The text has been thoroughly revised and substantially extended to enhance its value to the reader. All the basic skills of the quantity surveyor in construction procurement, contract administration and cost control and management are dealt with in sufficient detail to meet the needs of students. The newly developing areas of project management and value management are examined and illustrated in a practical way.